2008
DOI: 10.1016/j.joep.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Religion and trust: An experimental study

Abstract: We investigate the relationship between religion and trust. Using a questionnaire, we measure: i) general religiosity, and; ii) the extent of religious beliefs, experience, and ritual. These are then analyzed with behavior in a trust game (Berg et al., Games and Economic Behavior, 1995), which we also extend by providing information of a potential trustee's religiosity in certain tasks. We find that trusting increases with the potential trustee's religiosity. The extent to which trusting increases with a trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
206
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(223 citation statements)
references
References 33 publications
(28 reference statements)
14
206
3
Order By: Relevance
“…Our results are consistent with Anderson et al (2010) who found no association between religiosity measures and the Trust game. In contrast, Tan and Vogel (2008) did find a significant relationship between religiosity and trust. Their design gave information about the level of religiosity of the other players using a 5-point scale.…”
Section: Effect Of In-group Pairingcontrasting
confidence: 75%
See 2 more Smart Citations
“…Our results are consistent with Anderson et al (2010) who found no association between religiosity measures and the Trust game. In contrast, Tan and Vogel (2008) did find a significant relationship between religiosity and trust. Their design gave information about the level of religiosity of the other players using a 5-point scale.…”
Section: Effect Of In-group Pairingcontrasting
confidence: 75%
“…Religion also promoted trustworthiness; religious responders were more likely to send money back to proposers. In contrast to Tan and Vogel (2008), Anderson, Mellor, and Milyo (2010) found self-identified religious affiliation to be unrelated to behavior in Trust games, but found a weak association between church attendance and contributions in the Public Goods game. Participants who reported higher attendance of religious services offered 30% more, on average, than participants reporting lower church attendance.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…For example, participants demonstrated greater trust in the "trust game" with others who identified as religious (Tan & Vogel, 2008). Relatedly, people who signaled their Mental Representations of Atheists and Theists 5 religiosity, such as by fasting for religious reasons, were trusted more than people who did not signal their religiosity (Hall et al, 2015).…”
Section: Perceiving Religiosity In a Facementioning
confidence: 99%
“…Since the pioneered study, many literatures discuss, and other issues derived such like religion participation and income, economic development, social trust, labor supply, market competition, education choice etc, but these empirical studies focus on Europe and America mostly. Fewer studies analysis the influence of religion in Chinese world and the empirical samples were limited in specific village or regions and cause less representative in the study outcome [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%